(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Inclusive education constitutes a unique field in pedagogy and didactics (Escobar et al., 2020), since it allows the development of thoughts and cognitive processes, in which individualities are recognized, the learning rhythms of each student and the teaching levels of each teacher, in our specific case in the area of ​​mathematics. Our general purpose is aimed at promoting strategies that ensure quality learning in students and teachers at multigrade schools in a Rural context, through didactic suitability, personal and institutional meanings, semiotic functions, semiotic conflicts, and genesis of the Metric System. Decimal, in this way, the link with the local context or identity and the cooperation with the subjects of their environment are identified, in order to generate innovative models. The methodology used was qualitative (Bisquerra, 2009), with a case study (Stake, 2020), which was executed from a coherent trajectory for the appropriation of the research results, from this the conclusion was obtained. the incorporation of the medium, the suitability assessment guides and the signification processes as an important instrument for the teacher to achieve a didactic transposition in his classroom.